The Effect of Increased Plant Protein Intake on the Lipid Profile of Chronic Kidney Disease Patients: A Meta-Analysis of Controlled Clinical Trials - Papaodyssea, Ioanna; Lagiou, Areti; Tzoulaki, Ioanna; Valanou, Elisavet; Naska, Androniki (Nutrients, 2025)
Background/Objectives: Chronic kidney disease (CKD) is associated with increased mortality, with cardiovascular disease (CVD) being the primary cause of death. Proper lipid regulation may reduce CVD risk and slow CKD progression. While there is evidence that a higher plant protein intake could ameliorate lipid levels in the general population, the effects of this dietary regimen within the CKD population remain uncertain, with studies providing conflicting results. We aim to investigate the impact of increased plant protein intake on the lipid levels of CKD patients. Methods: Two electronic databases (PubMed, Scopus) were reviewed for controlled clinical trials assessing the effect of increased plant protein intake versus the usual CKD animal-based diet in CKD patients, published until June 2024. Results: Eleven trials, encompassing 248 patients, were included in this meta-analysis. Overall, compared to the usually recommended CKD diet, increased plant protein intake was associated with statistically significant reductions in total cholesterol (−24.51 mg/dL, 95% CI −40.33, −8.69), low-density lipoprotein (LDL) (−21.71 mg/dL, 95% CI −38.32, −5.1), triglycerides (− 21.88 mg/dL, 95% CI −35.34, −8.40), and Apolipoprotein B levels (−11.21 mg/dL, 95% CI −18.18, −4.25). No significant changes were observed in high-density lipoprotein (HDL) (0.09 mg/dL, 95% CI −1.82, 1.99) and Apolipoprotein A levels (0.04 mg/dL, 95% CI −7.14, 7.21). Conclusions: Increased plant protein intake, mainly from soy, reduces total cholesterol, LDL, triglycerides, and ApoB in adult CKD patients. Further research is needed to assess these effects in dialysis patients and explore non-soy plant sources.